STELARR Volume IV—Latin America: Opportunities for rangelands restoration through livestock value chains - Bravo, Aura; Burkart, Stefan (International Livestock Research Institute, 2025)
Sustainable livestock value chains in Latin America’s rangelands offer significant restoration and economic opportunities. However, success depends on aligning standards, ensuring equitable community participation, and fostering private-public investment models to maximize environmental and social returns across the region’s diverse rangeland landscapes. Sustainable Investments for Large-Scale Rangelands Restoration (STELARR) provides an in-depth overview of key livestock value chains for camelids (vicuna, guanacos, alpacas, and llamas) beef, sheep and goats amongst other, and highlights the challenges and opportunities for achieving sustainable production and explores their potential to reverse rangeland degradation, reduce poverty, and create inclusive livelihoods, particularly for women and youth. The private sector is beginning to adopt regenerative practices through product certifications (e.g., Responsible Alpaca Standard) aimed at supporting biodiversity and sustainable soil management. Currently, the benefits of such certifications favor large exporting firms over local communities, presenting an opportunity for community-based models and investment partnerships.